Deciphering pro-lymphangiogenic programs during mammary involution and postpartum breast cancer - Borges, Virginia F.; Elder, Alan M.; Lyons, Traci R. (Frontiers in Oncology, 2016)
Postpartum breast cancers are a highly metastatic subset of young women’s breast cancers defined as breast cancers diagnosed in the postpartum period or within 5 years of last child birth. Women diagnosed with postpartum breast cancer are nearly twice as likely to develop metastasis and to die from breast cancer when compared with nulliparous women. Additionally, epidemiological studies utilizing multiple cohorts also suggest that nearly half of all breast cancers in women aged <45 qualify as postpartum cases. Understanding the biology that underlies this increased risk for metastasis and death may lead to identification of targeted interventions that will benefit the large number of young women with breast cancer who fall into this subset. Preclinical mouse models of postpartum breast cancer have revealed that breast tumor cells become more aggressive if they are present during the normal physiologic process of postpartum mammary gland involution in mice. As involution appears to be a period of lymphatic growth and remodeling, and human postpartum breast cancers have high peritumor lymphatic vessel density (LVD) and increased incidence of lymph node metastasis (1, 2), we propose that novel insight into is to be gained through the study of the biological mechanisms driving normal postpartum mammary lymphangiogenesis as well as in the microenvironment of postpartum tumors.